FORMULASI SEDIAAN TABLET LEPAS LAMBAT TEOFILIN DENGAN MATRIKS ETILSELULOSA DAN XANTHAN GUM DENGAN METODE SIMPLEX LATTICE DESIGN - , Suprapto, S.Si., Apt ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Asthma drug theophylline as suitable formulated in sustained-release tablet dosage forms because it can ensure patient satisfaction and compliance with the matrix system. The purpose of this study was to determine the effect of EC and XG matrix combined with lactose to the physical properties, the release pattern and release kinetics, as well as to get the formula of slow-release theophylline tablets are optimum in terms of physical properties, followed zero-order release pattern and drug release kinetics. In this study, made 7 (seven) combined formula EC, XG and lactose are designed with the optimization model of simplex lattice design. Tablets prepared by wet granulation method. Evaluation of the homogeneity of the mixture of granules, granule flow properties, physical properties of tablets and tablet dissolution. Data processed by the software Design-Expert 8.0.4. Total release of theophylline from matrix tablets compared to the provisions of USP volume 32. Dissolution test data on each tablet compared to formula X which is a sustained-release preparation products on the market. The results showed that the more weight XG tablets increasingly uniform and combined EC-XG-lactose the most in decreasing coefficient of variance (CV) of the tablet weight